Penerapan Terapi Massage Kaki Terhadap Penurunan Kecemasan Pada Asuhan Keperawatan Pasien Dengan Kasus Hipertensi Di RSUD Poso: Application Of Foot Massage Theraphy To Reducing Anxiety In The Nursing Care Of Patients With Hypertension Cases At Poso Hospital - Sukmawati Said; Agusrianto Agusrianto (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction: Hypertension is a disease that not only has a physical impact but can affect psychological conditions such as anxiety. Anxiety will have an impact on increasing the patient's blood pressure. For this reason, nursing actions can be given such as foot massage to reduce the anxiety of patients with hypertension. The purpose of this study was to describe nursing care with the application of foot massage therapy to reduce anxiety in nursing care for patients with hypertension cases at Poso Hospital. Method : The research method is using a descriptive method with a case study approach. The study subjects were hypertensive patients with anxiety problems. Result : The results of the study Mrs. L revealed pain in the head and nape, the pain felt like stabbing, Mrs. L said she felt anxious when blood pressure increased and felt worried if the disease got worse and complications occurred, blood pressure 173/120 mmHg. Nursing problems are acute pain, anxiety and activity intolerance. Implementation is carried out for 4 days. Evaluation after implementation of the application of foot massage therapy there are changes with the results of client anxiety decreasing from moderate anxiety to mild anxiety, clients feel more relaxed and comfortable and blood pressure decreases 140/100 mmHg. Conclusion : The conclusion that the application of foot massage therapy can reduce anxiety in hypertensive patients. Suggestions patients can do foot massage independently according to what the researcher teaches.